Faculty perspectives using practice-based teacher education in physical education - DERVENT, FATİH (My University, 2023)
Purpose: Practice-based teacher education (PBTE) has been proposed as an approach to combat forms of teacher education that create prescriptive understandings of teaching that are disconnected from practice. In physical education, PBTE is becoming more prevalent. Some have argued that many of its elements have been in use for some time, whereas other elements have been refined or are new. In this study, we were motivated to examine the use of PBTE by physical education teacher educators and their perceptions of PBTE. Method: Participants were nine teacher educators from the United States (n = 6), Turkey (n = 2), and Belgium (n = 1). Surveys were used to gather data on the use of PBTE and the perceptions of teacher educators. Data describing the use of PBTE in their programs were descriptively analyzed. Our perceptions were interpreted using an intrinsic case study with PBTE serving as the case. Findings: Programs adopted similar and different elements of PBTE. Four themes emerged relative to the perceptions of teacher educators about PBTE: (a) how the context of the teacher educator influences their use of PBTE, (b) teacher educators’ use of PBTE, (c) the advantages of using PBTE, and (d) a critical analysis of PBTE. Conclusion: Our approach to operationalizing PBTE may help encourage useful conversations in physical education teacher education.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Surgery Medicine Sciences; Orthopedics and Traumatology; Social Sciences and Humanities; Sociology; Education; Health Sciences; Klinik Tıp (MED); Sosyal Bilimler (SOC); Klinik Tıp; Sosyal Bilimler Genel; REHABİLİTASYON; ORTOPEDİ; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Clinical Medicine (MED); Social Sciences (SOC); CLINICAL MEDICINE; SOCIAL SCIENCES, GENERAL; REHABILITATION; ORTHOPEDICS; EDUCATION & EDUCATIONAL RESEARCH; Ortopedi ve Spor Hekimliği; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Sosyal Bilimler ve Beşeri Bilimler; Orthopedics and Sports Medicine; Physical Therapy, Sports Therapy and Rehabilitation; Social Sciences & Humanities; core practices; physical education teacher education; preservice teachers; teacher education pedagogies